Childhood Trauma Associated with Enhanced High Frequency Band Powers and Induced Subjective Inattention of Adults - Lee, Seung-Hwan; Park, Yeonsoo; Jin, Min Jin; Lee, Yeon Jeong; Hahn, Sang Woo (Frontiers in Behavioral Neuroscience, 2017)
Childhood trauma can lead to various psychological and cognitive symptoms. It has been demonstrated that high frequency EEG powers could be closely correlated with inattention. In this study, we explored the relationship between high frequency EEG powers, inattention, symptoms of adult attention deficit hyperactivity disorder (ADHD), and childhood traumatic experiences. A total of 157 healthy Korean adult volunteers were included and divided into two groups using the Childhood Trauma Questionnaire (CTQ) score. The subjective inattention scores, ADHD scale, and anxiety and depression symptom were evaluated. Electroencephalogram (EEG) was recorded and quantitative band powers were analyzed. The results were as follows: 1) the high CTQ group showed significantly increased delta, beta1, beta2, beta3, and gamma, and significantly decreased low alpha power compared to the low CTQ group, 2) the high CTQ group had higher inattention score compared to the low CTQ group, 3) the high CTQ group had higher adult ADHD scores, 4) CTQ scores showed significant positive correlations with inattention scores, and adult ADHD scores, 5) unexpectedly, the inattention scores showed significant positive correlations with beta powers and a negative correlation with low alpha power, and 6) The moderated mediation model was confirmed: the depression fully mediated the path from state anxiety to inattention, and the CTQ significantly moderated the pathway between anxiety and depression. Our results show the possibility that childhood adversity may cause subjective inattention and adult ADHD symptoms. Depressive symptoms fully mediated the path from anxiety to inattention, especially in those who report severe childhood